PEMBUATAN MATERNITY JACKET SEDERHANA SEBAGAI ALAT PERAGA PRAKTIKUM PEMERIKSAAN TINGGI FUNDUS UTERI DENGAN METODE LEOPOLD - Dian Kartikasari; Catur Anita Sari; Niken Kumala Budi (JOMIS (Journal of Midwifery Science), 2023)
Uterine fundal height measurement using Leopold method is the one of the learning outcome in antenatal care course that must be achieved by midwifery students. For practical teaching in laboratory, the lecturer and the students usually use a phantom with synthetic rubber material. As it made of synthetic rubber, this phantom become stiff and lack of real tactile sensation to measure fundal height. This research aimed to make a simple maternity jacket as practical teaching aid which fabricable and affordable so the students can determine the fundal height boundary. This study used research and development method. The number of respondents was 32 with purposive sampling and 2 experts. This research taken place in Midwifery Laboratory of Poltekkes Kemenkes sorong from April to November 2021. The research instrument use questionnaire. The data was analyzed by converting the qualitative form to quantitative using Likert scale, and the mean score result was converted back to qualitative form. Feasibility analysis by calculating the score of the respondents’ assessment results compared to the ideal score. The results showed that the respondents strongly agreed that this product is feasible with feasibility percentage of 96.5%. Based on the results of the assessment, it is expected that this product can be used as a practical teaching aid and can improve students' skills in fundal height measurement. Further research is needed for the development of this practical teaching aids so that it can be used for a complete Leopold examination.